Book Reviews. Issue 1 (1st March 2023) - Carlson, Rebecca; Saglam, Erol
Abstract : Adriana Petryna, Horizon Work: At the Edges of Knowledge in an Age of Runaway Climate Change, Princeton, NJ: Princeton University Press, pp. 224, 2022 Sertaç Sehlikoglu, Working Out Desire: Women, Sport, and Self-Making in Istanbul, Syracuse, NY: Syracuse University Press, pp. 339, 2021